Estimation of the drift velocity of Equatorial Plasma Bubbles using GNSS and digisonde data - Navas-Portella Víctor; Altadill David; Blanch Estefania; Altadill Mar; Segarra Antoni; de Paula Víctor; Timoté Cristhian Camilo; Juan José Miguel (Journal of Space Weather and Space Climate)
Equatorial Plasma Bubbles (EPBs) play a crucial role in modulating plasma density and electron content within the equatorial ionosphere. In this work, we present an advanced and more robust version of the method developed by Blanch E et al. (2018, J Space Weather Space Clim., 8, 38–32) for detecting EPBs using data from the Global Navigation Satellite System (GNSS). The enhancements introduced in this version significantly improve the EPB detection process, achieving a notable reduction in the false positive rate compared to the previous approach. These refinements include the application of more rigorous statistical techniques to achieve a more accurate fit for the background Total Electron Content (TEC), leading to better characterization of EPBs through improved estimation of disturbance shapes. Applying the capabilities of this new method in a dense network of GNSS sensors, we have developed an interferometric procedure for estimating EPB drift velocities, including both speed and direction. This procedure provides valuable insights into the dynamic behavior of EPBs in the Caribbean region during 2014. Our analysis reveals a predominant eastward propagation pattern of EPBs, closely aligned with modified dip isolines. Furthermore, by integrating the results from the GNSS-based method with quasi co-located digisondes, we applied a conceptual model to estimate EPB velocities along their drift direction. This model has been tested across different geographical sectors and validated through comparisons with results from other independent studies. This cross-verification confirms the reliability of the methods for capturing EPB characteristics. This approach improves the precision of EPB detection and contributes to a deeper understanding of their spatiotemporal dynamics and behavior, providing a valuable framework for characterizing these phenomena in the equatorial ionosphere.